2010
DOI: 10.1186/1749-8090-5-36
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic cardiovascular dysregulation as a potential mechanism underlying depression and coronary artery bypass grafting surgery outcomes

Abstract: BackgroundCoronary artery bypass grafting (CABG) is often used to treat patients with significant coronary heart disease (CHD). To date, multiple longitudinal and cross-sectional studies have examined the association between depression and CABG outcomes. Although this relationship is well established, the mechanism underlying this relationship remains unclear. The purpose of this study was twofold. First, we compared three markers of autonomic nervous system (ANS) function in four groups of patients: 1) Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
0
17
0
2
Order By: Relevance
“…Besides psychological factors and behavioral factors Ziegelstein et al, 2000), endothelial dysfunction (Celano and Huffman, 2011;Pizzi et al, 2009), increased platelet activity (Celano and Huffman, 2011;Schins et al, 2004), autonomic nervous system dysfunction (Dao et al, 2010;Kop et al, 2010) and inflammation are possible factors having a role in the interaction between cardiovascular disease and depression. For this review we will focus on inflammation.…”
Section: Inflammation As a Link Between Depression And Cardiovascularmentioning
confidence: 99%
“…Besides psychological factors and behavioral factors Ziegelstein et al, 2000), endothelial dysfunction (Celano and Huffman, 2011;Pizzi et al, 2009), increased platelet activity (Celano and Huffman, 2011;Schins et al, 2004), autonomic nervous system dysfunction (Dao et al, 2010;Kop et al, 2010) and inflammation are possible factors having a role in the interaction between cardiovascular disease and depression. For this review we will focus on inflammation.…”
Section: Inflammation As a Link Between Depression And Cardiovascularmentioning
confidence: 99%
“…length of stay at the hospital (Dao et al, 2010). Another example was that having depressive symptoms prior to injury was a risk factor for poor affective/behavioral, cognitive, and mental health-related quality-of-life outcomes in patients after mild traumatic brain injury (Kumar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the physiological profile of a Coronary Artery Bypass Grafting patients with Post-Traumatic Stress Disorder may be complicated given purported research that low Heart Rate Variability is related to cardiovascular disease (van der Kolk, 2006). As previously discussed, it has been reported that patients with Coronary Artery Disease and a diagnosis of Post-Traumatic Stress Disorder have lower Heart Rate Variability than those patients with Coronary Artery Disease alone (Dao et al, 2010a;Krittayaphong et al, 1997;Stein et al, 2000). Since Post-Traumatic Stress Disorder and cardiovascular disease are associated with decreased Heart Rate Variability and Autonomic Nervous System dysregulation, Heart Rate Variability biofeedback training may reduce complications post-surgery.…”
Section: Treatment Using Heart Rate Variabilitymentioning
confidence: 92%
“…Specifically, long term treatments are unrealistic and unfeasible given the sudden onset of Coronary Artery Bypass Grafting surgeries (Doerfler et al, 1994). Since there is evidence that patients suffering from Post-Traumatic Stress Disorder have an increased likelihood of mortality following Coronary Artery Bypass Grafting surgery (Dao et al, 2010a), in combination with length of treatment necessary for effective Post-Traumatic Stress Disorder care, there is a necessary need for an effective, short term treatment for improving outcomes following Coronary Artery Bypass Grafting surgery. As mentioned earlier, Heart Rate Variability is a measure which examines the interplay between the parasympathetic and sympathetic influences on heart rate and represents the psychophysiological mechanism of emotion regulation (Appelhans & Luecken, 2006).…”
Section: Treatment Using Heart Rate Variabilitymentioning
confidence: 99%